Evaluation of post-extraction healing after atraumatic extraction in gutka chewers and non-gutka chewers using the modified inflammation proliferation remodeling scale - Abdul Hafeez Shaikh; Saira Hassan Askarey; Amynah Charania Shaikh; Syed Jaffar Abbas Zaidi; Raheel Memon; Fatima Rafi Lari; Saadullah Iqbal (BMC Oral Health, 2024)
Abstract Background Gutka, a smokeless tobacco mixture containing tobacco and areca nut, is widely consumed in South Asia and impairs wound healing due to vasoconstrictive and cytotoxic effects. Wound healing assessment in oral surgery lacks standardisation, and phase-specific evaluation tools are seldom used. This study aimed to compare post-extraction healing after atraumatic tooth extraction in gutka chewers and non-chewers using the modified Inflammation Proliferation Remodeling (IPR) scale to validate this scale for clinical use. Methods A prospective cohort study at a dental college in Karachi, Pakistan, included 200 participants aged 18–45 undergoing atraumatic extraction of premolars or molars, divided into gutka chewers (n = 100) and non-chewers (n = 100). The modified IPR scale was developed and validated using content validity assessment by experts, pilot testing, inter-rater reliability (Cohen’s kappa), and internal consistency (Cronbach’s alpha). Wound healing was assessed using the validated modified IPR scale immediately post-extraction (Day 0), at the proliferative phase (Day 7), and the remodelling phase (6 weeks). Statistical analyses included Mann-Whitney U tests, multivariate linear regression, and Spearman’s correlation. Results The modified IPR scale demonstrated good content validity, substantial inter-rater reliability (Cohen’s kappa 0.80–0.86), and good internal consistency (Cronbach’s alpha 0.84). No significant difference in IPR scores was observed between groups during the inflammatory phase (Day 0). Gutka chewers had significantly higher IPR scores during the proliferative phase (mean 5.9 ± 1.6 versus 4.2 ± 1.2; p < 0.001) and the remodelling phase (mean 3.6 ± 1.2 vs. 2.1 ± 0.9; p < 0.001), indicating delayed healing. Gutka use was a significant predictor of delayed healing (B = 1.2, p < 0.001) after adjusting for age and gender. Duration of gutka use positively correlated with higher IPR scores during the proliferative (rho = 0.46, p < 0.001) and remodelling phases (rho = 0.51, p < 0.001), reflecting a dose-dependent effect. The questionnaire was effectively validated with an 80% response rate and a 90.9% completion rate. Conclusions Gutka chewing is significantly associated with delayed post-extraction wound healing, with longer duration correlating with poorer outcomes. The modified IPR scale was effectively validated and proved to be a reliable tool for assessing wound healing progression, demonstrating its utility in clinical practice and research settings. Dental professionals should consider gutka use when planning patient care, and public health initiatives should aim to eliminate gutka consumption to improve oral health outcomes.